Redescription of the largest ice bug, Namkungia magnus com. nov. (Grylloblattodea, Grylloblattidae) from Korea - Kim, Byung-Woo; Lee, Woncheol (Zootaxa, 2006)
The largest ice bug species, Namkungia magnus (Namkung, 1986) from Balgudeuk cave at Jeongseon, Gangwon-do, Korea is transferred from the genus Galloisiana and redescribed with setae and trichobothria patterns, and with mouthpart, basisternum and genital structure descriptions based on the morphological characters. This species resembles N. biyongensis (Namkung, 1974) by its large size (longer than 30 mm), eyeless condition, more than 47antennomeres, and 12 cercomeres but is distinguished by asymmetrical supra-anal plate of the bulging 9th abdominal tergite with truncate projection, 52 antennomeres, the cervical sclerite with nine setae (11 on right) on the lateral margin of the left, and copulatory sclerites of the genital structure.